Archaeofaunal Remains, Geography, and the Investigation of Cultural Keystone Places - Steve Wolverton; Jonathan Dombrosky; Chelsey Geralda Armstrong; Susan C. Ryan (Ethnobiology Letters, 2025)
Cultural Keystone Places (CKPs) are areas on the landscape crucial to individual and group identities, especially descendant communities. As such, they are often significant components of Indigenous land claims and cultural continuity. CKPs commonly have deep temporal roots and unclear spatial boundaries, and archaeological investigation is often relied upon to define them. However, relying on archaeological prospection and data to define a CKP can be problematic. The discovery of archaeological material and, by extension, a CKP is a probabilistic endeavor, often constrained by preservation conditions and sampling strategies. While many archaeologists understand that the material record will always be incomplete and that the absence of archaeological materials does not indicate the absence of a CKP, this view is juxtaposed with comparatively simple legal or regulatory understandings of CKPs as areas exclusively defined by either the presence or absence of archaeological materials in places such as British Columbia, Canada, which we discuss in this paper. To frame that discussion, we turn to the archaeological record from a different region; we use a large multisite database from southwestern Colorado—created and curated by the Crow Canyon Archaeological Center—to illustrate the variability in the quality of the archaeological record across the landscape. By modeling the fragmentation and sample size of animal remains, we demonstrate how even systematically collected archaeological data can still lead to knowledge gaps, potentially resulting in a false negative for the presence of a CKP. We therefore urge regulatory agencies to more thoroughly consider the sampling strategies and preservation conditions of remains related to the investigation of CKPs and to highlight the value of using robust archaeological databases to support Indigenous land rights and the identification and protection of CKPs.